POLLUTION OF COASTAL AREAS OF JAKARTA BAY: WATER QUALITY AND BIOLOGICAL RESPONSES - Kunzmann, Andreas; Arifin, Zainal; Baum, Gunilla (Marine Research in Indonesia, 2018)
Coastal development, growing urbanization and industrialization are the most important stressors of coral reefs worldwide. Jakarta is one of the largest megacities worldwide. The coral reefs of the Thousand Islands north of Jakarta have degraded dramatically over the last 30-40 years. While large-scale gradients (i.e., regional drivers) have been extensively studied and shown shifts and declines in coral cover and composition, local drivers and their impact on spatial community composition have been neglected. The aim of our study is to investigate the spatial impact of anthropogenic stressors on local and regional scales on coral reefs north of Jakarta. Our results demonstrate that reefs in the north of the Thousand Islands are separated from the reefs in Jakarta Bay (JB), where a direct impact of Jakarta can be seen. Local anthropogenic effects rather than regional gradients have shaped a spatial patchwork of differentially degraded reefs along the nearshore islands. The main anthropogenic stressor is pollution and sedimentation rate, NO2, PO4 and chlorophyll-a explain over 80% of the variation. Surfactants and diesel-borne compounds from sewage and bilge water discharges are common pollutants. Responses to combinations of selected pollutant with elevated temperature (+3Â°C) were determined in the metabolic performance of the coral reef fish Siganus guttatus. During combined exposure, metabolic depression was observed. Effects of pollutants were not amplified by elevated temperature. In a study about two dominant soft coral genera, Sarcophyton spp. and Nephthea spp., on dissolved inorganic nutrients (DIN), turbidity (NTU), and sedimentation combined with measurements of photosynthetic yield and respiratory electron system (ETS) activity water quality seems to control the relative abundance and physiology of dominant soft corals in JB. In order to reverse or prevent phase shifts from hard to soft corals, there is a need to manage the water quality better. It is concluded that the intense anthropogenic pressure from local as well as regional sources is responsible for the spatial structure and health of reefs. Therefore, improved spatial management with a focus on both local and regional stressors is needed for effective marine conservation.